All Writers Are Border Walkers: Emma Donoghue Between History and Fiction in Astray and The Woman Who Gave Birth to Rabbits - Milda Danytė (Baltic Journal of English Language, Literature and Culture)
Historical fiction has gained a degree of popularity among readers in the last two decades it has not enjoyed since the fashion for writing novels about national history was set by Sir Walter Scott in the early 19th century. Later in that same century, however, the value of historical fiction as such was challenged by historians who were eager to make history a science; they claimed that academic historical writing provided an objective view of the past based on archival research and was therefore fundamentally superior to historical novels. A devaluation of historical fiction took place which is still felt today. In the context of this opposition of history and fiction, Emma Donoghue’s recent historical fiction offers a fresh approach to the genre. The aim of this article, after reviewing the issue of its relationship to history, is to analyze Donoghue’s innovative combination of fiction and the archive in two collections of short historical fiction, The Woman Who Gave Birth to Rabbits (2002) and Astray (2012). Donoghue’s own reflections on her work are applied in this analysis, as well as the theoretical approach to this kind of fiction by Lubomir Doležel.